2017
DOI: 10.1002/cctc.201700097
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Surfactants through the Hydroaminomethylation of Terpenes

Abstract: A catalytic system was developed to enable the use of industrially available terpenes (e.g., β‐myrcene, β‐farnesene) in hydroaminomethylation to obtain renewable building blocks for surfactants in two steps. This homogeneously catalyzed tandem reaction includes both hydroformylation and enamine condensation steps, followed by hydrogenation. Under the optimized conditions, the Rh/1,2‐bis(diphenylphosphino)ethane catalytic system delivers products in high yields (70 %) after short reaction times (3 h) with unpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Another terpene that is a promising building block for valuable chemicals is β‐farnesene, which has recently become available on a larger scale. It is produced by yeast fermentation and has attracted attention in both academic and industrial research and development. Since the large and bulky substituent is located at the 2 nd position, the 1,3‐diene unit is prone to conversion with nucleophiles, even during telomerization with amines .…”
Section: 3‐dienesmentioning
confidence: 99%
“…Another terpene that is a promising building block for valuable chemicals is β‐farnesene, which has recently become available on a larger scale. It is produced by yeast fermentation and has attracted attention in both academic and industrial research and development. Since the large and bulky substituent is located at the 2 nd position, the 1,3‐diene unit is prone to conversion with nucleophiles, even during telomerization with amines .…”
Section: 3‐dienesmentioning
confidence: 99%
“…Hydroformylation of the internal double bonds is much more difficult than the terminal bonds, thus it is not surprising that the examples mentioned above are related to isolated terminal double bonds. In the only reported hydroaminomethylation of a conjugated terpene [81] regioselectivity in hydroformylation was low along with low catalytic activity per se explained by formation of relatively stable η3-allyl-Rh complexes [78].…”
Section: Hydroaminomethylation Of Olefin Bonds In Terpenesmentioning
confidence: 96%
“…A few examples of hydroaminomethylation reaction with terpenes were reported including α-pinene [75], β-pinene [74], camphene [74], limonene [74,76,77], β-myrcene and β-farnesene [78] and naturally occurring allyl benzenes such as eugenol [79] and estragole [80]. Hydroformylation of the internal double bonds is much more difficult than the terminal bonds, thus it is not surprising that the examples mentioned above are related to isolated terminal double bonds.…”
Section: Hydroaminomethylation Of Olefin Bonds In Terpenesmentioning
confidence: 99%
“…Hydroformylation of β ‐myrcene was reported to yield different unsaturated C11‐aldehydes depending on the ligand . Our research group has found an efficient way to convert β ‐myrcene into an efficient surfactant via an enamine by means of hydroaminomethylation (Figure ) . Surfactants offer a wide range of applications, e. g. as a detergent and food additive as well as in oilfield chemistry…”
Section: C6 Molecules (Renewables)mentioning
confidence: 99%
“…The combination of [Rh(cod)Cl] 2 (cod=1,5‐cyclooctadiene) with a 1,2‐bis (diphenylphosphino) ethane (DPPE) ligand shows product yields of 70 % after short reaction times of 3 hours. Furthermore, regioselectivities of 97 % were observed in the hydroformylation stage …”
Section: C6 Molecules (Renewables)mentioning
confidence: 99%